Proximity effect and interface transparency in Al/InAs-nanowire/Al diffusive junctions. (24th August 2017) - Bubis, A V; Denisov, A O; Piatrusha, S U; Batov, I E; Khrapai, V S; Becker, J; Treu, J; Ruhstorfer, D; Koblmüller, G
Abstract: We investigate the proximity effect in InAs nanowire (NW) junctions with superconducting contacts made of Al. The carrier density in InAs is tuned by means of the back gate voltage V g . At high positive V g the devices feature transport signatures characteristic of diffusive junctions with highly transparent interfaces—sizable excess current, re-entrant resistance effect and proximity gap values ( Δ N ) close to the Al gap ( Δ 0 ). At decreasing V g, we observe a reduction of the proximity gap down to Δ N ≈ Δ 0 / 2 at NW conductances ∼ 2 e 2 h − 1, which is interpreted in terms of carrier density dependent reduction of the Al/InAs interface transparency. We demonstrate that the experimental behavior of Δ N is closely reproduced by a model with rectangular potential barrier at the Al/InAs interface.